Frontal view of the equestrian statue of King Edward VII - Ghosh, Ayan (2023)
The equestrian statue of King Edward VII was sculpted by Sir Joseph Edgar Boehm (1834-90). It was donated to the city by industrialist and philanthropist Albert David Sassoon (1818-96) who commissioned it to mark Edward's visit to India in 1875-76 when he was the Prince of Wales. Edward succeeded Queen Victoria as the English monarch in 1901.